Respuestas
Respuesta dada por:
1
- { 8 + [ 4 - ( 2 - 1 ) + 6 ] - 3 } =
- { 8 + [ 4 - 2 + 1 + 6 ] - 3 } =
- { 8 + 4 - 2 + 1 + 6 - 3 } =
8 - 4 + 2 - 1 - 6 + 3 =
+ | -
8 | -4
2 | -1
3 | -6
_____
13| -11
+13 -11 = +2
- { 8 + [ 4 - 2 + 1 + 6 ] - 3 } = +2
- { 8 + [ 4 - 2 + 1 + 6 ] - 3 } =
- { 8 + 4 - 2 + 1 + 6 - 3 } =
8 - 4 + 2 - 1 - 6 + 3 =
+ | -
8 | -4
2 | -1
3 | -6
_____
13| -11
+13 -11 = +2
- { 8 + [ 4 - 2 + 1 + 6 ] - 3 } = +2
chicalobo:
¡Espero que sea la mejor que tengas!
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años